Variation of Splice Length with Bending Behavior of Reinforced Concrete Beams - Sulastri S.; Ilham Nurhuda; Antonius A. (Universitas Islam Sultan Agung, 2019)
The splice length of the distribution depends on the concrete stress with reinforcement, generally the bond stress is tested by pull out testing where pull out testing can provide a good comparison between the efficiency of the attachment of various types of reinforcement surfaces. However, the bending behavior of the beam is very different from the pure tensile pull out test. This study presents the effects of variations of lap splice (30db, and 40db) in the area of beam pull. The first test object was a beam BN - 0 (non splice length) which was a normal beam. The second test object was a beam BN - 30db with the splices length(ld) of 480 mm and the third test object was a 40db beam with the splice length (ld) of 640 mm. The test used a pure bending test method with loading of Two Point Loads on a simple support beam. The results gained from this study obtained flexural capacity in BN-0 (non lap splices) of 115.15 kN, flexural capacity of BN - 30db of 90.484 kN, and beam flexural capacity of BN-40db of 124.848 kN. The displacement ductility at BN-30db decreased 35% to BN-0 and displacement ductility at BN-40db increased 48% to BN-0, the bond strength attached to BN-40db increased 2.92% to BN-30db. The splice length (ld) 40db was able to develop the ability to achieve yield stress loads and the spread of crack concentration around the joints.